2017
DOI: 10.1016/j.chemphyslip.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the structural organization of a novel low-density lipoprotein nanoparticle reconstituted with docosahexaenoic acid

Abstract: Low-density lipoprotein nanoparticles reconstituted with unesterified docosahexaenoic acid (LDL-DHA) is promising nanomedicine with enhanced physicochemical stability and selective anticancer cytotoxic activity. The unique functionality of LDL-DHA ultimately relates to the structure of this nanoparticle. To date, however, little is known about the structural organization of this nanoparticle. In this study chemical, spectroscopic and electron microscopy analyses were undertaken to elucidate the structural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Interestingly, LDL reconstructed from unesterified DHA exhibited higher physicochemical stability and selective anti-cancer cytotoxic activity. Mulik et al [ 79 ] analyzed the structure of the nanoparticles. They found that unesterified DHA preferentially added to the outer surface of LDL, where the anionic carboxyl terminal of DHA was exposed to the LDL surface, gave the surface of the nanoparticles a negative electric charge.…”
Section: Delivery Systems Of Dhamentioning
confidence: 99%
“…Interestingly, LDL reconstructed from unesterified DHA exhibited higher physicochemical stability and selective anti-cancer cytotoxic activity. Mulik et al [ 79 ] analyzed the structure of the nanoparticles. They found that unesterified DHA preferentially added to the outer surface of LDL, where the anionic carboxyl terminal of DHA was exposed to the LDL surface, gave the surface of the nanoparticles a negative electric charge.…”
Section: Delivery Systems Of Dhamentioning
confidence: 99%
“…Extensive physicochemical and morphological characterization of the LDL- nanoparticles has been reported previously by our group ( 31 , 39 ). In the following study the LDL-DHA nanoparticles displayed an average hydrodynamic diameter of 30.1 ± 0.5 nm and a negative zeta potential of -23.4 ± 0.9 mV.…”
Section: Resultsmentioning
confidence: 85%
“…To determine the effect of DHA supplementation on EGFR-dependent growth, we utilized a DHA-based therapeutic consisting of DHA free fatty acid inserted into human LDL particles ( 26 ). Each LDL nanoparticle is devoid of cholesterol, contains approximately 1,100 unesterified DHA fatty acid molecules (LDL-DHA), and is approximately 22 nm in diameter ( 38 ). These nanoparticles have been shown to preferentially and efficiently target liver cancer versus noncancer cells in vitro ( 26 , 39 ) and reduce proliferation of xenografts of hepatocellular carcinoma (HepG2) in vivo.…”
Section: Resultsmentioning
confidence: 99%